AESTHETICS AND TECHNICAL TREATMENTS IN CONTEMPORARY ADVERTISING DESIGN - Noor Adnan Oleiwi, Batool Radhi Kadhim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The style old term in the language and served a wide area in various aspects of life and commonly used in the arts field " as Ibn Khaldun to see the manner in which the woven structures or template that emptied it" while the word used Style To denote the machine by which writing is done, and it has become a term that means the method of writing, and the style has become widely used in various areas of life based on the multiplicity of its concepts. It has a floating concept. It is a simple aspect of the articulated at times and it is a conscious art from the art of the designer at other times, which is an expression issued by the nature of The human being therefore always transcends the limits on which he closed , and the style is an approach distinguished from another, such as the style of the designer, the style of the era, or the style of the director, and this wide use made it difficult to define it with a definition, as it refers to the nature of the human being himself as ((the appearance of the saying that results About the designer’s choice of the means of expression, these means that are determined by the nature of the person speaking or the director)) , or what leads to saying that each style is "an image of its owner." That is, each designer has his own style, which is a form that indicates the artist and bears his qualities as an indication of the artistic work of the creator, and these works become an image indicating that they refer to that artist, and the artwork becomes a method that shows his thinking and how he looks at things and explains them. The new, influential and eloquent in selecting and employing the techniques and linguistic means to express the thought that is embodied in the live interaction with the recipient in a way through which he realizes that this expression has acquired an approach that can only be created by this creator, and with the development of civilization and the advancement of human thought, it has made these concepts sciences in their own right. It is subject to scientific systems and deep and accurate analytical approaches that research and study the process of conveying ideas, and from here the need to study the style has become a given, as a catalyst in identifying the nature of this or that creator and a center for studying the human mind in terms of thought, perception and understanding, and the characteristics of the method are defined by three elements. Essential "clarity, strength and beauty" , the design work that is characterized by clarity, strength and beauty is subject to an authentic experience and sincere feelings in expression by the artist full of For his experience in employing and organizing the elements of artistic work on new intellectual foundations that necessarily lead to the crystallization of a new and distinct style that earns the artist his peculiarity that distinguishes him from other artists in terms of the artistic movement.